2003
DOI: 10.1074/jbc.m210244200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoenolpyruvate-dependent Tubulin-Pyruvate Kinase Interaction at Different Organizational Levels

Abstract: Evidence for the direct binding of pyruvate kinase to tubulin/microtubule and for the inhibitory effect of phosphoenolpyruvate on tubulin-enzyme hetero-association were provided by surface plasmon resonance and pelleting experiments. Electron microscopy revealed that pyruvate kinase induces depolymerization of paclitaxel-stabilized microtubules into large oligomeric aggregatesandbundlesthetubulesinasaltconcentrationdependent manner. The C-terminal "tail"-free microtubules did not bind pyruvate kinase, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Precipitated proteins were separated by SDS-PAGE followed by immunoblotting. Co-pelleting assays were performed as described previously (28). Briefly, extracts from MDCK cells treated with colcemid or paclitaxel were centrifuged at 100.000 ϫ g for 20 min (Rotor RP55-S; M120 Microultracentrifuge, Sorvall, Kendro Laboratory Products GmbH, Langenselbold, Germany).…”
Section: Immunoprecipitation and Co-pelleting Assaysmentioning
confidence: 99%
“…Precipitated proteins were separated by SDS-PAGE followed by immunoblotting. Co-pelleting assays were performed as described previously (28). Briefly, extracts from MDCK cells treated with colcemid or paclitaxel were centrifuged at 100.000 ϫ g for 20 min (Rotor RP55-S; M120 Microultracentrifuge, Sorvall, Kendro Laboratory Products GmbH, Langenselbold, Germany).…”
Section: Immunoprecipitation and Co-pelleting Assaysmentioning
confidence: 99%
“…In support of this hypothesis, several glycolytic enzymes are known to regulate MT assembly. For example, PK destabilizes MTs and impedes MT assembly [Vertessy et al, 1999;Kovacs et al, 2003]. PFK from Dictystelium discoideum is also an inhibitor of MT polymerization [Orosz et al, 1999].…”
Section: Metabolic Enzymes and Regulators Also Contribute To Regulatimentioning
confidence: 99%
“…2. For phosphoglucose isomerase [Walsh et al, 1989], aldolase [Walsh et al, 1989;Volker et al, 1995], triosephosphate isomerase (TPI) [Orosz et al, 2000], glyceraldehyde-3-phosphate dehydrogenase (GAPDH) [Walsh et al, 1989;Somers et al, 1990;Volker et al, 1995;Andrade et al, 2004;Chuong et al, 2004], phosphoglycerate kinase (PGK) [Walsh et al, 1989], and pyruvate kinase (PK) [Walsh et al, 1989;Volker et al, 1995;Kovacs et al, 2003], binding has been demonstrated by copelleting with MTs. In the case of TPI, binding of the native protein is relatively weak, but a mutant form found in a human disease shows much greater to binding to MTs [Orosz et al, 1999].…”
Section: Most Glycolytic Enzymes Bind Mtsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tubulin cytoskeleton has also been proposed as being intimately related to metabolic activity. Glyceraldehyde-3-phosphate dehydrogenase can interact with microtubules to bring them together (104,243,270); triosephosphate isomerase, hexokinase, phosphofructokinase, pyruvate kinase, and aldolase interact with microtubular proteins and a hyperstructure can exist in which enzyme properties and fluxes are altered (210); and pyruvate kinase hinders microtubule assembly in vitro unless phosphoenolpyruvate is present (124).…”
Section: Hyperstructures Send and Receive Messages Via Their Constitumentioning
confidence: 99%